Analysis of Seasonal Patterns in the Performance of Fuel Markets in the Visegrad Group - Krawiec, Monika; Górska, Anna (Comparative Economic Research. Central and Eastern Europe, 2024)
The objective of the paper is to examine seasonal patterns in the performance of fuel markets in the Visegrad Group (V4) countries (i.e., the Czech Republic, Hungary, Poland, and Slovakia). Unlike numerous papers that investigate global oil markets, this study focuses on regional retail fuel markets. The dataset consists of weekly Pb95 gasoline and diesel prices from January 2016 through December 2020. The methods applied cover a range of statistical and econometric tools, such as the Wilcoxon rank sum test, simple regression, and the generalized autoregressive conditional heteroscedasticity (GARCH) models. The research refers to important calendar effects such as the month‑of‑the‑year effect and the Halloween effect, but it also considers the seasonal gasoline transition effect. The empirical analysis presented in this paper does not bring clear evidence for significant seasonal patterns in the performance of fuel markets in the Visegrad Group as the application of different methods provides mixed results. Nevertheless, the findings of the Wilcoxon test are consistent with the GARCH (1, 1) estimates, which detected an April effect for gasoline and a December effect for diesel in Poland. The simple regression and GARCH (1, 1) estimates are consistent for an October effect for gasoline in Slovakia. None of the methods applied allows us to find a significant Halloween effect, a reverse Halloween effect, or a gasoline seasonal transition effect on the fuel markets of the Visegrad Group. These findings bring new insight into the V4 fuel markets and may be important for oil processing firms, retail traders, transport and distribution companies, farmers, and individual consumers.